2017
DOI: 10.1039/c7ra06306g
|View full text |Cite
|
Sign up to set email alerts
|

A dual-faced interlayer prepared by electron beam evaporation for enhanced-performance lithium–sulfur batteries

Abstract: In this work, a dual-faced carbon paper was prepared by depositing Al2O3 on one side of carbonized filter paper via the technique of electron beam evaporation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…[41] With the addition of the electrolyte additives, the peaks located at 531.7-532.1, 529.2-530.8, and 532.2-532.5 eV are referred to O 2− , OH − and C─O, respectively. [28,42,43] These O peaks result from the reaction on Al anode.…”
Section: Resultsmentioning
confidence: 99%
“…[41] With the addition of the electrolyte additives, the peaks located at 531.7-532.1, 529.2-530.8, and 532.2-532.5 eV are referred to O 2− , OH − and C─O, respectively. [28,42,43] These O peaks result from the reaction on Al anode.…”
Section: Resultsmentioning
confidence: 99%
“…To solve these issues, various strategies such as design of the cathode, 6‐10 modification of the separator, 11,12 and optimization of the electrolyte 13‐15 have been used. Interlayer inserted between the separator and the cathode is one of the most effective methods to enhance the conductivity and confine polysulfides 16,17 . For example, Zhuang et al 18 designed a novel interlayer using MoO 2 ‐decorated carbon nanofibers (MoO 2 ‐CNFs membrane) for Li‐S batteries, which can trap polysulfides through strong polar surface interaction and rapid redox reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Interlayer inserted between the separator and the cathode is one of the most effective methods to enhance the conductivity and confine polysulfides. 16,17 For example, Zhuang et al 18 designed a novel interlayer using MoO 2 -decorated carbon nanofibers (MoO 2 -CNFs membrane) for Li-S batteries, which can trap polysulfides through strong polar surface interaction and rapid redox reaction. Shi et al 19 reported a conductive and polar niobium nitride (NbN), which is in-situ introduced onto graphene with ultrasmall size and high dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth mentioning that various metal oxides have been employed to modify separators, because of their strong chemical bonding with the migrating LiPs. To date, many metal oxides (such as RuO 2 [15], TiO 2 [16][17][18], Al 2 O 3 [19,20], SnO 2 [21], V 2 O 5 [22], and MnO 2 [23]) have shown the ability to suppress shuttling of LiPs, resulting in decreased capacity decline and better electrical performance of the Li/S battery. For example, Evers et al [5] coated nanosized TiO 2 particles on the separator, which increased the cycling performance of the Li/S battery [5].…”
Section: Introductionmentioning
confidence: 99%